The effect of singing learning method on children's language and social emotional development - Sakia, Andini Putri; Karta, I Wayan; Rachmayani, Ika (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2024)
Education has an important role for the future development of children and determinants of progress in a nation. This study aims to find the effect of the treatment of the implementation of the singing learning method on the language and social-emotional development of group B children. The type of research used was experimental, quantitative approach, and one group pretest-posttest design with 23 children as research subjects. Data collection techniques in the form of observation, documentation, and data analysis techniques in the form of paired samples tests with the help of the SPSS version 16 program. Based on the results of the research conducted, there are differences in language and social emotional development between before the treatment of the implementation of singing learning methods and after the treatment of the implementation of singing learning methods. Language and social emotional development after the treatment of the implementation of singing learning methods is higher than before, this is evidenced by the average pre-test results of language development 51.60 and the average post-test results of language development 70.00 for the average pre-test results of social emotional development 37.78 and and the average post-test results of social emotional development 56.47. It is concluded, there is an effect of the treatment of the implementation of the singing learning method on the language and social emotional development of group B children at TK Negeri 1 Taliwang, West Sumbawa, Indonesia.